Rethinking transparency in public service media: a multidimensional framework for better governance - Van den Bulck, Hilde; Horowitz, Minna; Raats, Tim (Frontiers in Communication, 2025)
Transparency has become a cornerstone of public service media (PSM) governance yet it remains inconsistently understood and applied. Increased scrutiny from various stakeholders has resulted in a need for actionable and meaningful transparency. Scholarly evidence highlights transparency’s benefits and risks, including potential misuse, as illustrated with current examples from Finnish PSM organization Yle and tVRT in Flanders (Belgium). This brief provides a multidimensional framework for actionable transparency efforts that allow PSM to move beyond ad hoc, reactive and partial approaches by elaborating key dimensions of transparency about what, when, how, by whom and to whom, transparency is required. Recommendations include fostering transparency practices that are meaningful and resistant to weaponization and politicization, developing participatory governance models, and leveraging transparency as a tool for organizational resilience.